The Orthodox Church Back to Progress - Maican, Petre (2018)
There is an increased tendency inside the Orthodox Churches to reject the socio-cultural changes brought about by postmodernity and seek the restoration of an idealized past. In this article, I argue against this trend and set the premises for a constructive Orthodox engagement with secular postmodernity. Initially, I point out that in the patristic frame of thought, the movement of history receives a positive value as part of God's plan to lead humankind to deification. In order to show how this motion towards deification can be discerned in a modern setting, I turn to Dumitru Staniloae, who interpreted and applied the patristic vision of history in the context of communist Romania. Using Staniloae's criteria for evaluating the communist regime, I suggest that Orthodoxy and postmodernity might have more in common than what was initially thought and argue for a re-evaluation of the Orthodox approach to the major tropes of postmodernity.
Keywords: Dumitru Staniloae; Orthodox Church; Romania; Communism; History; Progress